2013
DOI: 10.1007/s10072-013-1483-9
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potentials, clinical evaluation, and imaging findings in multiple sclerosis

Abstract: Vestibular-evoked myogenic potentials (VEMP), short-latency electromyographic responses elicited by acoustic stimuli, evaluate the function of vestibulocollic reflex and may give information about brainstem function. The aim of the present study is to evaluate the potential contribution of VEMP to the diagnosis of multiple sclerosis (MS). Fifty patients with MS and 30 healthy control subjects were included in this study. The frequency of VEMP p1-n1 and n2-p2 waves; mean p1, n1, n2, and p2 latency; and mean p1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Also none of the patients had history/current symptoms/signs of peripheral vestibular disease that could influence VEMP results. Two studies have shown that conduction block is the most frequent pathology amongst MS patients and that conduction block of the cVEMP is more frequent in patients with vestibular symptoms and a higher EDSS . The current study has shown that MS patients with clinically evident brainstem involvement have a significantly higher percentage of conduction block in both oVEMP and cVEMP responses compared with MS patients without clinically evident brainstem involvement.…”
Section: Discussionsupporting
confidence: 56%
“…Also none of the patients had history/current symptoms/signs of peripheral vestibular disease that could influence VEMP results. Two studies have shown that conduction block is the most frequent pathology amongst MS patients and that conduction block of the cVEMP is more frequent in patients with vestibular symptoms and a higher EDSS . The current study has shown that MS patients with clinically evident brainstem involvement have a significantly higher percentage of conduction block in both oVEMP and cVEMP responses compared with MS patients without clinically evident brainstem involvement.…”
Section: Discussionsupporting
confidence: 56%
“…Regarding the design, eight (29%) studies were descriptive (5)(6)(16)(17)(18)28,(30)(31) ,19 (68%) were comparative cross-secti onal (7)(8)(9)(10)(12)(13)(14)(15)(19)(20)(21)29,(32)(33)(34)(35)(36)(37)(38) , and one (3%) was longitudinal cohort (39) .…”
Section: Methods Characterization Applicationmentioning
confidence: 99%
“…Some reports described abnormal VEMP responses in MS patients, including latency extensions and even non-responses. [3][4][5][6][7][8]11,12,18] However, latency extension in the VEMP test and unresponsiveness also occur in those with acoustic neurinomas and Meniere's disease; such abnormalities are not specific to MS. Thus, the proportion of MS patients exhibiting abnormal VEMP responses widely varies (i.e., from 18 to 100%).…”
Section: Tr-entmentioning
confidence: 99%
“…The cVEMP is a marker for the integrity of the vestibulocollic reflex (VCR) pathway and the oVEMP denotes the integrity of the vestibuloocular reflex (VOR) pathway. [7][8][9] The VEMPs show a problem in the reflex pathway, even in the absence of a topographic analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation